PENGARUH LAMA FERMENTASI TERHADAP KANDUNGAN PROTEIN SUSU KEFIR SEBAGAI BAHAN PENYUSUN PETUNJUK PRAKTIKUM MATA KULIAH BIOKIMIA - Susanti Susanti; Sri Utami (UNIVERSITAS PGRI MADIUN, 2014)
Highly content of nutrition in milk a perfect for microba to grow. Microba can pollute the milk fastly so it can not be consume. Fermentation is one way to avoid the milk decay. Fermentation of milk is conducted by inoculating pasteurized milk with kefir grains additional as cultur starter. The objective of this research is knowing the effect of fermentation period toward protein content of kefir milk as material to compile guideline book for lab work in biochemistry class. The research is quantitative with RAL factorial 4x1 in 3 times repetition. The factors of research are fermentation in 0 hour (t1), 12 hours (t2), 24 hours (t3), 36 hours (t4). Research use titration formol to collect the data of protein content. Anava one tail is used to examine the hypothesis continued with BNT examination. The result of hypothesis shows that sig t (fermentation period) for protein content in kefir milk 0,000 with significance degree is 0,05. It shown that sig t < 0,05. From the result above, the conclusion is fermentation period affect the protein content in kefir milk.